(untitled) (Acta Scientiarum. Health Sciences, 2012)
Regional odontodysplasia is an uncommon, nonhereditary developmental dental disorder of unknown etiology, which should be early detected. This paper compares a regional odontodysplasia case with the clinical and radiographic characteristics reported in the literature, showing a 1y6m follow up and the limitations of performing a multidisciplinary esthetic and functional treatment.